Mucus‐Penetrating Nanosuspensions for Enhanced Delivery of Poorly Soluble Drugs to Mucosal Surfaces. Issue 21 (26th September 2016) - Yu, Tao; Chisholm, Jane; Choi, Woo Jin; Anonuevo, Abraham; Pulicare, Sarah; Zhong, Weixi; Chen, Minmin; Fridley, Colleen; Lai, Samuel K.; Ensign, Laura M.; Suk, Jung Soo; Hanes, Justin
Abstract : Mucus‐penetrating nanosuspensions, consisting of pure hydrophobic therapeutics with dense muco‐inert coatings that enable particles to effectively bypass the mucus barrier, demonstrate superior drug distribution and absorption at mucosal surfaces. With significantly increased drug load compared to polymeric systems and established clinical translation of nanosuspensions‐based products, mucus‐penetrating nanosuspensions are a promising vehicle for improving mucosal delivery of poorly soluble drugs.